Systematic Variation of Pyrrolobenzodiazepine (PBD)-Dimer Payload Physicochemical Properties Impacts Efficacy and Tolerability of the Corresponding Antibody–Drug Conjugates - Staben, Leanna R; Chen, Jinhua; Cruz-Chuh, Josefa dela; del Rosario, Geoff; Go, Mary Ann; Guo, Jun; Khojasteh, S. Cyrus; Kozak, Katherine R; Li, Guangmin; Ng, Carl; Lewis Phillips, Gail D; Pillow, Thomas H; et al. (Journal of medicinal chemistry, 2020)
Cytotoxic pyrrolobenzodiazepine (PBD)-dimer molecules are frequently utilized as payloads for antibody–drug conjugates (ADCs), and many examples are currently in clinical development. In order to further explore this ADC payload class, the physicochemical properties of various PBD-dimer molecules were modified by the systematic introduction of acidic and basic moieties into their chemical structures. The impact of these changes on DNA binding, cell membrane permeability, and in vitro antiproliferation potency was, respectively, determined using a DNA alkylation assay, PAMPA assessments, and cell-based cytotoxicity measurements conducted with a variety of cancer lines. The modified PBD-dimer compounds were subsequently incorporated into CD22-targeting ADCs, and these entities were profiled in a variety of in vitro and in vivo experiments. The introduction of a strongly basic moiety into the PBD-dimer scaffold afforded a conjugate with dramatically worsened mouse tolerability properties relative to ADCs derived from related payloads, which lacked the basic group.